Effect of Azolla spp on growth performance and yield of paddy / Nor Idayu Mohamad Rabi - Mohamad Rabi, Nor Idayu (Faculty of Plantation and Agrotechnology, 2019)
Rice has staple food sources to Malaysian and also as main income sources to many farmers in Malaysia. However, from year to year, the yield of paddy was decrease due to few factors and one of them is the low input of fertilizer especially nitrogen. The pure culture of Azolla spp was used to study the effect on growth performance and yield of paddy as Azolla spp was containing mechanical function that can help the uptake of nutrients. Azolla spp also supply the nitrogen for paddy growth as it has a symbiotic relationship with the nitrogen-fixing cyanobacteria Anabaena azollae. The experiment was conducted using Completed Randomized Design (CRD) with two treatments and five replication. Not incorporated with Azolla spp (T0) and (T1) incorporated with Azolla spp. NPK fertilizer was applied on all replication by same amount and watered regularly. Various parameters were taken such as plant height, number of leaves, number of tiller, fresh weight, and 1000 grain weight of rice plant. The result revealed after 10 weeks of experiment. By using Azolla spp on paddy, there is significant increases on the growth of paddy plant. The result show no significant on paddy height but show significant difference in paddy leaves and tiller due to the influence of Azolla spp. This study will attract many parties especially farmers to use Azolla biofertilzers for paddy cultivation.